2019
DOI: 10.1101/649111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunoinformatics Prediction of Epitope Based Peptide Vaccine Against Listeria Monocytogenes Fructose Bisphosphate Aldolase Protein

Abstract: Listeria Monocytogenes represents an important food-borne pathogen worldwide that can cause lifethreatening listeriosis disease especially in pregnant women, fetuses, elderly people, and immuno-compromised individuals with high mortality rates. Moreover, no vaccine against it exists. This study predicts an effective epitope-based vaccine against Fructose 1,6 Bisphosphate Aldolase (FBA) enzyme of Listeria Monocytogenes using immunoinformatics approaches. The sequences were retrieved from NCBI and several predic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…While other studies had focused only on specific proteins of C. perfringens ( 71 , 72 ), we consider that analyzing the whole proteome could reveal novel more immunogenic proteins. We followed three approaches to propose vaccine candidates: a whole-protein based vaccine, a protein-subunit based vaccine, and a multi-epitope protein vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…While other studies had focused only on specific proteins of C. perfringens ( 71 , 72 ), we consider that analyzing the whole proteome could reveal novel more immunogenic proteins. We followed three approaches to propose vaccine candidates: a whole-protein based vaccine, a protein-subunit based vaccine, and a multi-epitope protein vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study conducted by de Klerk et al [79] showed that the Fba1 protein has the ability to provoke immune responses in human against M. mycetomatis [79]. Also, several recent publications have used the Fba1 protein as a strong antigenic target for predicting Band T-cell epitopes in order to design promising vaccines against fungal and bacterial pathogens such as M. mycetomatis, P. aeruginosa, L. monocytogenes, and S. mansoni by using in silico tools [80][81][82][83]. Hence, there are more studies to explore the fructose bisphosphate aldolase protein immunogenic role and the possibility to find common conserved epitopes for different organisms.…”
Section: Discussionmentioning
confidence: 99%